187 Getting it right first time: CT coronary angiography first in GP patients referred to racpc – is it feasible?. (4th June 2021) - Graby, John; Murphy, David; Metters, Rhys; Porter, Katy; Parke, Kady; Boden, Eleanor; Khumalo, Mzimkhulu; Jones, Samantha; Ellis, Dawn; Lowe, Rob; Rodrigues, Jonathan
Abstract : Introduction: The Rapid Access Chest Pain Clinic (RACPC) targets rapid investigation, symptom relief and improved outcomes for patients with potential coronary artery disease (CAD). NICE recommends CT coronary angiography (CTCA) first line for all new onset chest pain patients without known CAD, unless pain is non-anginal with a normal ECG. Getting It Right First Time reviews variations in service delivery to improve care, outcomes and efficiency. The RACPC pathway may be compared with 2 week wait cancer services, where investigation follows GP assessment prior to considering secondary care review. In an era of assessing existing pathways to improve the patient journey, treatment and efficiency, this study aimed to test the hypothesis that an upfront CTCA strategy is feasible and safe for GP referrals to RACPC. Methods: A single-centre retrospective review of consecutive RACPC GP referrals September-October 2019, excluding known CAD or unavailable notes. An upfront CTCA following 'referral based triage' strategy ( figure 1 ) was compared to existing face-to-face review and decision making. An analysis of referral content was made to facilitate safe central triage and cross-referenced with RACPC review and management. Time to diagnosis and hospital encounters were compared. Results: 107/172 patients met review criteria: median age 60 (IQR 22); 52 (49%) male. GP Referral vs RACPC: Table 1 compares GP referral and RACPC findings. Of referrals without CAD history, no prior CAD was identified at RACPC review. All murmurs at referral were confirmed at RACPC. 17 (16%) patients had murmurs newly identified at RACPC though none had ≥moderate disease. Actual management vs hypothetical pathway: 74 CTCAs were requested via RACPC vs 61 via a hypothetical pathway, the difference relating to requests outside of NICE guidance. This would extrapolate to a reduction of 78 CTCAs annually. Upfront CTCA cuts the time from referral to RACPC (median 27 days [IQR 16.5]). Actual median time from referral to diagnosis combining all investigation pathways was 77 days (IQR 28), or 81 days (IQR 25) for obstructive CAD. This reduced by a median 22 days with the hypothetical pathway. 23 (21%) patients with actual RACPC management had no CAD identified, representing pathways where 1 encounter (CTCA) may have been sufficient, which extrapolates to 138 less RACPC appointments annually (£21, 666 in current NHS tariffs). 32 (30%) patients had non-obstructive CAD and were discharged via letter. Conclusion: A novel pathway with a referral-based triage to upfront CTCA ± subsequent RACPC would have been safe and efficient. The modelled reduction in hospital encounters would be cost effective and, importantly, enable the RACPC to review risk factors after identification of non-obstructive CAD. This improves treatment for a key group at risk of future events, particularly in those with aggressive CAD phenotypes on CTCA, whilst streamlining patients with obstructive CAD. Conflict of Interest: Nil